O sector económico da cultura na Área Metropolitana de Lisboa. aspectos locativos e implicações nas políticas urbanas - Henriques, Eduardo Brito (Finisterra, 2000)
CULTURAL INDUSTRIES IN THE LISBON METROPOLITAN AREA: LOCATION FEATURES AND IMPLICATIONS ON URBAN POLICIES - This paper aims to examine the current situation and the recent development of cultural industries in the Lisbon Metropolitan Area in view of the increasing international interest in this area.Two main conclusions emerged from the analysis. Firstly, we concluded that cultural industries are steadily increasing, showing rates above the Lisbon Metropolitan Area avarage in other industries. Secondly, a high degree of concentration of activities and jobs could also be observed mainly within the city of Lisbon. However one of the most important trends of the sector in recent years has been the deconcentration of activities with the development of different specialisations in the peripheral areas. The implications of this on urban policies are analysed in the last section of this paper.